Understanding the spatio-temporal behaviour of riverine plastic transport and its significance for flux determination: insights from direct measurements in the Austrian Danube River - Pessenlehner, Sebastian; Gmeiner, Philipp; Habersack, Helmut; Liedermann, Marcel (Frontiers in Earth Science, 2024)
Plastic pollution in aquatic environments is a growing concern, with rivers recognized as major pathways. However, rivers themselves are also subject to pollution. Hence, understanding riverine plastic transport dynamics is essential for mitigating environmental impacts. Although plastic-related research focus has shifted from marine environments towards rivers, challenges remain in standardizing methods for monitoring and integrating spatio-temporal variabilities of riverine plastic occurrence into flux determination. This study addresses these challenges by adopting established methods from sediment research. Utilizing data from a net-based cross-sectional multi-point approach, it examines spatio-temporal and discharge-dependent variations. It comprehensively analyzes the complex dynamics of plastic transport in the Danube River, contrasting an impounded section near Aschach, Austria, with a free-flowing reach near Hainburg, Austria. The paper emphasizes the significance of applying these methodologies for accurate flux determination and underscores the risks of neglecting them. By incorporating average microplastic particle weights, we aim to overcome limitations in prior methodologies that solely emphasize qualitative aspects or rely on item numbers. Spatial distribution analysis revealed a pronounced stratification at low flow and a more variable distribution in the free-flowing section, attributed to higher turbulence. As discharge increased, vertical mixing occurred, along with distinct lateral patterns displaying increased concentrations toward the riverbanks. Encountering plastic particles throughout the river profile underscores their properties of both suspended and floating matter, emphasizing the importance of hydro-morphology and multi-point cross-sectional measurement approaches. Microplastic loads were calculated to be <6.9 t a -1 in Aschach and <17.1 t a -1 in Hainburg, compared to total plastic loads of <14.3 t a -1 in Aschach and <41.6 t a -1 in Hainburg. Consequently, plastic loads were doubled to tripled within the Austrian section of the Danube River. The study contributes valuable insights into the complex nature of plastic transport in river systems, emphasizing comprehensive spatial, temporal and discharge-dependent assessments for characterizing and managing plastic pollution. It suggests that rivers can function as sources, pathways and sinks of plastic pollution, contingent upon hydro-morphological conditions.